1991
DOI: 10.1515/zna-1991-1-214
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Reorientation in Liquid Methanol

Abstract: Oxygen-17 enriched methanol CD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 0 publications
6
30
0
2
Order By: Relevance
“…The experimental data exhibit a faster growth for τ 2,w OH in comparison with results of the simulation models under study. For pure methanol, Ludwig et al [39] reported τ 2, m OH = 5.1 ps, but mentioned that the simulation results are quite sensitive to the force field, thus leading to a value in the wide interval of 2-5 ps. Our value for methanol is slightly less than 3 ps, showing a faster relaxation than apparently it comes out from the experiment.…”
Section: Dynamic Propertiesmentioning
confidence: 99%
“…The experimental data exhibit a faster growth for τ 2,w OH in comparison with results of the simulation models under study. For pure methanol, Ludwig et al [39] reported τ 2, m OH = 5.1 ps, but mentioned that the simulation results are quite sensitive to the force field, thus leading to a value in the wide interval of 2-5 ps. Our value for methanol is slightly less than 3 ps, showing a faster relaxation than apparently it comes out from the experiment.…”
Section: Dynamic Propertiesmentioning
confidence: 99%
“…A number of recent investigations have reported molecular correlation times for water, simple alcohols and binary solutions of alcohols that are based on the measurement of proton spin lattice relaxation times of oxygen-17 enriched samples [1][2][3][4][5] . For protonated samples the spin-lattice relaxation rate, R1, for protons interacting with other protons is given by the dipolar relaxation equation: …”
Section: Introductionmentioning
confidence: 99%
“…Deuterium relaxation time experiments are attractive since the deuterium quadrupole coupling constant, χD, is typically ten times greater than dipolar coupling; consequently, intermolecular interactions can be ignored. For a spin-1 nucleus such as 2 H the relaxation rate, R 1 is given by:…”
Section: Introductionmentioning
confidence: 99%
“…Several solid state NMR studies of single crystals of hydrated salts 3 and of single crystals of amino acids 4 have shown that the QCP is related to the inverse cube of the hydrogen-bond distance. Quite recently solution state NMR studies of water 5-7 and alcohols 8,9 have shown that the deuterium QCP depends in a sensitive way on the concentration and the temperature. The QCP, Q , is the product of the nuclear electric quadrupole moment, eQ, and the electric field gradient ͑EFG͒ at the nucleus, eq, that is,…”
Section: Introductionmentioning
confidence: 99%